Stretchable Transparent Conductors: from Micro/Macromechanics to Applications - Chen, Zhi Hong; Fang, Rui; Li, Wei; Guan, Jianguo (Advanced materials (Weinheim), 2019)
Stretchable transparent conductors (STCs), generally consisting of conducting networks and stretchable transparent elastomers, can maintain stable conductivity and transparency even at large tensile strain, beyond the reach of rigid/flexible transparent conductors. They are essential components in stretchable/wearable electronics for using on irregular 3D conformable surfaces and have attracted tremendous attention in recent years. This review aims to provide systematical correlation of the conducting element–substrate interaction with the structural stability of conducting networks, as well as the properties and device applications of STCs. It starts with the micromechanics for stretching of conducting elements on substrates, including the mechanical mismatch, distribution/level of interfacial shear stress, and the deformation behavior of conducting elements on substrates. The macromechanics for stretching of conducting networks on substrates are then further illustrated from a more statistical point of view, namely sliding/preferred orientation of percolation networks, unfolding of buckled structures, and unit cell distortion/distributed rupture of nanomeshes. The structure‐dependent properties as well as the state‐of‐the‐art applications of STCs are summarized before ending with the conclusions and outlooks for STCs. Stretchable transparent conductors (STCs) are key components of stretchable electronics. The conducting element–substrate interaction is systematically correlated with the structural stability of conducting networks, properties, and device applications of STCs. Special focus is put on the micromechanics of conducting elements on elastomers and the macromechanics of conducting networks. Conclusions and the outlook in this field are also presented.